Evolutionary-type estimates for the products of some powers of the inner radii of multiply connected domains - Zabolotnyi, Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.54We consider a classical problem of the geometric function theory concerning the maximum product of certain powers of the inner radii of $n$ mutually disjoint domains with respect to $n$ fixed points in the complex plane. For this product, several estimates of evolutionary type are established.